Review on Coastal Erosion, Displacement and Resettlement Strategies of South Asian Countries - Barua, Prabal; Rahman, Syed Hafizur; Mitra, Abhijit; Zaman, Sufia (The Global Environmental Engineers, 2020)
Coastal areas are subjected to unwelcome circumstances in the shape of sea-level rise and its adverse outcomes like storm surge, flooding and erosion with continuous climate change. In this manuscript, the authors presented the two case studies of erosion, displacement pattern and resettlement examples of climate displaced people of Bangladesh and India. Climate displaced people of Bangladesh and India have been an influx from coastal areas to a disaster-free safe area and also urban slum areas. In these circumstances, displaced people didn’t enjoy their cultural harmony, social status, family bondage in new living places. Resettled climate displaced people in the new habitat of Bangladesh and India are trying to adopting their new living conditions. Facilities of rehabilitation facilities have been evaluated to be insufficient and tiny for their sustenance in the long run. An appropriate development strategy is required by the Government so as to avoid the socio-economic backwardness of the resettlement areas of the South-Eastern coast of Bangladesh and Indian Sundarban inhabitants. The island inhabitants wait with great anxiety for help from the Government and Non-Government authorities to come frontward and support them to pull through their losses.